Increasing Serum Cholesterol Level among Sri Lankan Adult Obese Patients Admitted to Medical Wards: A Cross-sectional Study - R. (II) P. DIOSO; K. SHALINA; K. JUDENIMAL (Universitas Gadjah Mada, 2017)
This research identifid the factors affcting the widespread of the level of serum cholestrol among adult obese patients admitted to government hospitals in the easternpart of Sri Lanka, and identifie the number of adults obese patients with increasing serum cholesterollevel. A descriptive cross-sectional studydesign was used. Convenience sampling technique helped select 150 patients in medical wards and clinics of two government hospitals in the easternprovince of Sri Lanka, and Questionnaireswere distributedfor data analysis. Overall findingsof 150 obese patients regarding increasing serum cholestrol level admitted in the medical wards and follow-up at medical clinics had 59% in moderate risk, 36% with high risk, and 2% with a minimal risk of increasing serum cholestero level. Gender was a factor, which brings about 49.3% (n = 74) of the respondents were female and 50.7% (n = 76) were male. About 59% of participants had 130–159 mg/dl of total cholesterollevel while 36% had 160–189 mg/dl and 1% had lower than 100 mg/dl. It was also identifiedthat age and co-morbidities of obesity are factors that affect an increasing serum cholesterol level